Transforming physical education: online learning trough sport modification and mini-games - Yuni Astuti; Oyatra Utama Warda; Rizki Almauli; Rosmawati Rosmawati; Bayu Haryanto; Erianti Erianti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background. This study considers the low learning outcomes of students in the subject of modified sports and small games as a problem that is more caused by the lack of learning media facilities for students in online classes which causes them to be less able to understand the material provided.